DETEKSI GEN PENYANDI ADHESIN PADA VEROCYTOTOXIGENIC Escherichia coli (VTEC) ISOLAT SAPI (Detection of Gene Encoding Adhesin of Verocytotoxigenic Escherichia coli (VTEC) Isolated from Cattles) - Wahyu Prihtiyantoro; Hartatik Hartatik; Mitra Slipranata; Novra A. Sandi (Jurnal Kedokteran Hewan, 2016)
This study was aimed to perform phenotypic and genothypic characterization of Escherichia coli (E. coli), particularly VTEC strain isolated from cattle faeces. In this study, 25 E.coli isolated from faeces specimens and faeces base fertilizer of dairy and beef cattles were used. Examination were carried out using phenotypic and genothypic characterization which is specified for E coli VTEC strain. The result showed that 20 % samples of fresh faeces specimens were detected as VTEC strains and none of isolate was detected from faeces base fertilizer samples. From VTEC strains, could detect 16 % VT1 gene, 12 % VT2 genes and 8% of both. Detection on gene pyelonephritis-associated pilli (pap), S fimbrial adhesion (sfa), and afimbrial adhesion (afa) were found about 60%, 80% and 80%, respectively.